Development of Wheat With Hypoimmunogenic Gluten Obstructed by the Gene Editing Policy in Europe - Jouanin, Aurélie; Boyd, Lesley; Visser, Richard G. F.; Smulders, Marinus J. M. (Frontiers in Plant Science, 2018)
Coeliac Disease (CD) is an auto-immune reaction to gluten in 1-2% of the human population. A gluten-free diet, excluding wheat, barley and rye, is the only remedy. This diet is difficult to adhere to, partly because wheat gluten is added to many processed products for their viscoelastic properties. In addition, gluten-free products are less healthy and expensive. Wheat products containing only hypoimmunogenic gluten proteins would be a definitive solution. Various gluten peptides that trigger CD have been characterized. A single wheat variety contains around hundred gluten genes, producing proteins with varying numbers of epitopes. Gene editing using CRISPR/Cas9 can precisely remove or modify the DNA sequences coding for immunogenic peptides. Wheat with hypoimmunogenic gluten thus exemplifies the potential of gene editing for improving crops for human consumption where conventional breeding cannot succeed. We describe here, in relation to breeding hypoimmunogenic wheat varieties, the inconsistencies of applying GM regulation in Europe for gene-edited plants while mutation breeding-derived plants are exempted. We explain that healthy products derived from this new technology may become available in the US, Canada, Argentina and other countries but not in Europe, because of strict regulation of unintended GM risk at the expense of reduction the existing immunogenicity risks of patients. We argue that regulation of gene-edited plants should be based on scientific evidence. Therefore, we strongly recommend implementing the innovation principle. Responsible Research and Innovation, involving stakeholders including CD patient societies in the development of gene-editing products, will enable progress towards healthy products and encourage public acceptance.